PEMANFAATAN QUIZIZZ PAPER MODE UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT BAHAN AJAR BAGI GURU - Hakiki, Eggy Kurnia; Iskandar, Tatang (Universitas Islam 45 Bekasi, 2024)
Education is a fundamental necessity for every individual that must be fulfilled. Project-based learning is an effective approach for children to understand and express their ideas and concepts through real-world activities. Quizizz is an online digital platform that enables the creation of interactive quizzes, offering engaging learning experiences and assessments for students. Accessible via a web browser, Quizizz can be utilized both in classrooms and for homework assignments. At SDN Ridogalih 01, the primary issue identified was the lack of diversity in teaching materials, as existing resources predominantly relied on different types of conventional media. The proposed solution involved providing teachers with knowledge and training on developing instructional materials by optimizing the use of Quizizz Paper Mode. This approach aimed to help teachers create more engaging and varied learning materials while also facilitating student assessment. The community service method employed in this initiative involved conducting workshops and instructional sessions for teachers on the effective use of Quizizz Paper Mode. The outcome of this program demonstrated an improvement in teachers' understanding and skills in utilizing Quizizz Paper Mode, encouraging them to be more creative and innovative in designing interactive learning materials.